Reformulation of the Regulation of the Criminal Offence of Refusing to Testify as a Witness in the Reform of Indonesian Criminal Law - Hank Mengket, Stephen; Wijaya, Andika; Setyobowo Sangalang, Rizki; Nugraha, Satriya (Journal Evidence Of Law, 2026)
This study examines the reformulation of the criminal offence of refusing to testify under Indonesian criminal law and proposes a rights-based graduated liability model that reserves criminal punishment for deliberate and persistent refusal after procedural safeguards, witness protection, and less restrictive measures have proven ineffective. Employing normative juridical research with statutory and conceptual approaches, the study analyzes the National Criminal Code, criminal procedural law, relevant criminal law doctrines, and the legal framework governing witness rights and obligations through descriptive and prescriptive methods. The findings reveal that the existing regulation risks overcriminalization because it does not sufficiently distinguish between culpable refusal to comply with a lawful obligation, the lawful exercise of the privilege to refuse testimony (hak ingkar) or the privilege against self-incrimination, and excusable non-compliance arising from compelling force, serious threats, or objectively unavoidable circumstances. Although the criminalization of unjustified refusal possesses philosophical, sociological, and juridical legitimacy in protecting the administration of justice, its application must remain subject to the principles of legality, culpability, proportionality, subsidiarity, and human rights protection. As an ius constituendum, this study proposes a graduated regulatory framework consisting of procedural clarification and renewed summons, protection intervention where threats or vulnerability exist, proportionate non-penal compliance measures, and criminal sanctions only as an ultimum remedium. The theoretical novelty of this study lies in reconceptualizing refusal to testify through a rights-based criminalization framework that integrates the witness’s legal obligation to participate in judicial proceedings with the state’s reciprocal obligation to guarantee procedural rights and effective protection. This reformulation provides clearer normative boundaries for distinguishing punishable refusal from legally protected or excusable non-compliance, thereby strengthening legal certainty while preventing the overcriminalization of vulnerable witnesses.